BRAYUT TOURISM VILLAGE DEVELOPMENT STRATEGY BASED ON COMMUNITY BASED TOURISM (CBT) IN EFFORTS TO EMPOWER THE PANDOWOHARJO VILLAGE COMMUNITY - Warmansyah Harefa; Aris Sunarya; Amirul Mustofah (International Journal of Multidisciplinary Reseach, 2026)
The development of tourist villages is one of the strategies in accelerating the local economy and improving the welfare of rural communities. This study aims to analyze the development strategy of Brayut Tourism Village based on Community-Based Tourism for community empowerment. This study refers to the concept of community empowerment, namely Community Based Tourism (CBT) proposed by Yodchai Suansri (2003) with indicators of community participation, economic benefits, cultural preservation, environmental sustainability, and involvement in decision-making. Using a qualitative method through the Systematic Literature Review (SLR) approach, this study examined the scientific literature and related documents. Data analysis is carried out through reduction, classification, and interpretation. The results show that the implementation of the Brayut Tourism Village has internalized the principles of Community Based Tourism (CBT) with active participation in the management of homestays, tourism services, and cultural activities. In addition to the positive economic impact, these activities also preserve local values. The tourism village development strategy must prioritize increasing the capacity of human resources and strengthening management institutions. This step is critical to ensuring a structured and sustainable community-based tourism system.